The Public Relations Role of DISKOMINFO SUMUT to Building a Positive Image of North Sumatra Governor in The Digital Era - Chairunnisa Nasution; Rahmanita Ginting (Persepsi: Communication Journal, 2023)
A large amount of public opinion and negative issues about The Governor of North Sumatra Edy Rahmayadi in various conventional media and digital media has resulted in the rise of media crisis issues around him which are controversial in society. To mitigate this, The North Sumatra Province Communication and Information Service (Diskominfo Sumut) The institution that oversees regional public relationsis trying to continue to build and maintain a positive image of The Governor of North Sumatra. This study aims to explain The role of digital public relations, reveal The obstacles faced, and examine how content management is carried out by human practitioners of The North Sumatra Diskominfo. This study used a qualitative descriptive method with four informants from The North Sumatra Diskominfo. Data collection techniques were obtained through in-depth interviews, observation, and documentation. Data analysis was obtained from data reduction, data presentation, and conclusion. The results of this study prove that there is a digital public relations role for North Sumatra Diskominfo through media monitoring activities, podcast broadcasts, and live streaming on YouTube and Instagram accounts @infosumutku, as well as buzzers to fight haters. The obstacles experienced were in the form of The attitude and behavior of The Governor of North Sumatra who was firm and to The point so that they became targets for press bullying to be published as negative news. The use of digital media is also carried out on social media, Tiktok, to gain The support of The millennial generation and generation Z.